2020
DOI: 10.1038/s41598-020-63120-6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization of mainstream marijuana and tobacco smoke

Abstract: Recent increases in marijuana use and legalization without adequate knowledge of the risks necessitate the characterization of the billions of nanoparticles contained in each puff of smoke. Tobacco smoke offers a benchmark given that it has been extensively studied. Tobacco and marijuana smoke particles are quantitatively similar in volatility, shape, density and number concentration, albeit with differences in size, total mass and chemical composition. Particles from marijuana smoke are on average 29% larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 51 publications
1
45
0
1
Order By: Relevance
“…Conventional studies have led to protocols optimized for the analysis of a few targeted analytes or chemical classes. Instead, GC×GC has shown its advantages in the multiclass and high‐resolution analysis of a variety of analytes [105,106]. In a recent approach, a methodology involving the use of SBSE was employed for the multiclass metabolite profiling of cannabis inflorescences [107].…”
Section: Non‐targeted Analysis Applicationsmentioning
confidence: 99%
“…Conventional studies have led to protocols optimized for the analysis of a few targeted analytes or chemical classes. Instead, GC×GC has shown its advantages in the multiclass and high‐resolution analysis of a variety of analytes [105,106]. In a recent approach, a methodology involving the use of SBSE was employed for the multiclass metabolite profiling of cannabis inflorescences [107].…”
Section: Non‐targeted Analysis Applicationsmentioning
confidence: 99%
“…Johnson et al (2014) found that cigarette smoke particles have a spherical morphology with an average effective density of (1.18 ± 0.11) g cm À3 . Another study by Graves et al (2020) showed that effective densities of tobacco and marijuana smoke particles are independent of particle size above 150 nm, with effective densities of (0.99 ± 0.1) g cm À3 for tobacco and (0.90 ± 0.09) g cm À3 for marijuana. These values are also within the range (1.13 ± 0.07) g cm À3 of the values found in this study.…”
Section: Size Selected Effective Density Of Flaming and Smoldering Emmentioning
confidence: 99%
“…There is substantially less scientific research that has explored the chemical characterization of marijuana cigarette smoke and most studies have focused on determining cannabinoids in marijuana smoke and reported it to contain most of the same toxins, irritants and carcinogens commonly present in tobacco smoke. 29 For instance, when smoked, marijuana produces more tar with more concentrations of carcinogens such as benzo[a]pyrene as compared to tobacco smoke, and consequently it has been classified as a secondary carcinogen possessing 50% to 70% more carcinogenic polycyclic aromatic hydrocarbons such as benzo[a]anthracene, benzene and phenols in greater amounts alongside toxic gases and reactive oxygen species 20 times higher than in tobacco. 30 Notably, these variations in carcinogenic compound concentration in marijuana increase its probability of causing lung cancer in the same way tobacco does, and which has been credited as the leading cause of lung cancer.…”
Section: Emerging Chemicals From Marijuana and Their Cancer Potencymentioning
confidence: 99%
“…30 Notably, these variations in carcinogenic compound concentration in marijuana increase its probability of causing lung cancer in the same way tobacco does, and which has been credited as the leading cause of lung cancer. 29 Nevertheless, it can be presumed that smoking of marijuana is a precursor for respiratory disease and cancer similar to those caused by tobacco smoking, but on the other hand, there is minimal literature reporting or demonstrating that marijuana smoking causes cancer. 31 Furthermore, it has been suggested that marijuana smoke comprises of particulate matter that is harmful and carcinogenic when inhaled because it contains potent compounds such as volatile organics and aromatic amines.…”
Section: Emerging Chemicals From Marijuana and Their Cancer Potencymentioning
confidence: 99%
See 1 more Smart Citation